THE ROLE OF ISLAMIC DA'WAH AND THE IMPLEMENTATION OF SHARIA ON THE EXISTENCE OF MUSLIMS IN THE MALDIVES ISLANDS PAST AND PRESENT - Meirison, Meirison; Bukhari, Bukhari; Saharuddin, Desmadi; Muhammadi, Qasem; Mistarija, Mistarija (Islam Futura, 2024)
Writing this article aims to explain the development of Islamic da'wah in the Maldives Islands, which is unique and rarely found in other Muslim regions. So far, the Maldives is only known as a tourist spot. It is rarely known that all of the Maldives adhere to Islam. The British have also ruled the Maldives for 78 years, influencing the Maldives to some extent. What is the form of da'wah carried out by Abu al-Barakat, whose origins are still debated by historians? But what is clear is that he had a significant influence on the spread of Islam in the Maldives Islands, which is corroborated by classical sources such as the text attributed to Ibn Battuta and several contemporary books. We conducted a literature study on this paper, with a historical approach, by collecting data, verifying and analyzing the data thoroughly, and rewriting the results of the analysis inductively in a qualitative descriptive form. Islam spread in the Maldives peacefully without violence and continues to survive from Christian missionaries and Shiite sects who come to spread their views. Scholars say about the fiqh theory that faith in conscience will not be changed by the sins and heresies it commits.